Implications of Bankruptcy of Married Debtors on Authority and Asset Status in Marriage - Diana Rahmawati; Zakiyah Zakiyah (International Journal Labs, 2022)
Background: Individual debtor bankruptcy will be an interesting problem if the individual debtor is bound in a legal marriage. Of course, there will be certain legal consequences for the husband or wife of the bankrupt debtor Objective: The purpose of this study is to determine the legal consequences of bankruptcy on the authority of debtors who are bound by marriage and their partners and the legal consequences of assets in marriage. Methods: The research method used is a normative legal research method, which is prescriptive in nature. The analytical method used in this study is a qualitative analysis in order to answer the problems studied. Results: The results of the study show that firstly, the consequences of bankruptcy can affect the authority of the debtor couple, if the husband or wife of the debtor who is declared bankrupt does not make a marriage agreement for the separation of assets, then to represent him a Curator is appointed. Second: the legal consequences of bankruptcy on assets are influenced by the presence or absence of a marriage agreement and the purpose of the use of debt, whether for the personal interest of the debtor or the common interest will determine the status of the assets in the marriage as bankrupt assets, which will be used to pay the debtors' debts. bankruptcy against its creditors.